Amplification of Migratory Inhibition Factor Production During the First 48 Hours of Exposure to Antigen - Philp, James R. (1973)
When lymphocyte-macrophage suspensions from sensitized animals are preincubated with specific antigen for 24 or more h, the following results are observed. (i) In a standard capillary macrophage migration test, there is complete inhibition of migration. (ii) When the preincubated cell suspension is mixed in varying proportions with a similar suspension from nonsensitized animals and a macrophage migration test is performed, there is no linear relationship between the degree of inhibition of migration and the proportion of sensitized lymphocytes initially present. Inhibition thus appears to be an “all-or-none” effect. (iii) In spite of the second observation, increasing periods of preincubation with antigen result in increasing inhibition. (iv) These results suggest the existence of a complex amplifying mechanism operating within the early period of exposure to antigen. (v) To test the possibility that cell proliferation contributes to this amplification, cells from sensitized guinea pigs were irradiated with a dose of 1,000 rads prior to preincubation with antigen. Despite this dose, which virtually abolishes cell division in other systems, no diminution whatever in the amplification of inhibition was observed. These results suggest the existence of an early phase of increased production of migratory inhibition factor that is not dependent on cell division but that may be related to “recruitment” of nonsensitized lymphocytes.